1999
DOI: 10.1055/s-1999-12
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Staging of Esophageal Carcinoma: Miniprobe Sonography Versus Conventional Endoscopic Ultrasound in a Prospective Histopathologically Verified Study

Abstract: Compared with conventional endosonography using 7.5-MHz large diameter instruments, MPS enables: a) safe passage through high-grade malignant esophageal strictures, achieving b) higher accuracy rates for T staging, and c) similar rates for N staging. The use of MPS can also represent an improvement in the comfort and safety of patients. Moreover, miniprobe sonography is highly cost-effective compared with conventional endosonography. Thus, MPS appears to be a valuable addition to the armamentarium for staging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…Furthermore, the large diameter of the echoendoscope (1.2 cm) may prevent complete staging of stenotic tumors [17]. Recently, high-resolution miniprobes with 12.5-20 MHz have been developed that may help to overcome some of the problems encountered with conventional endosonography [4,8,11,16]. This study was performed to investigate the impact of endosonography on demand with miniprobes and conventional EUS on the staging of upper GI tumors.…”
mentioning
confidence: 99%
“…Furthermore, the large diameter of the echoendoscope (1.2 cm) may prevent complete staging of stenotic tumors [17]. Recently, high-resolution miniprobes with 12.5-20 MHz have been developed that may help to overcome some of the problems encountered with conventional endosonography [4,8,11,16]. This study was performed to investigate the impact of endosonography on demand with miniprobes and conventional EUS on the staging of upper GI tumors.…”
mentioning
confidence: 99%
“…14,15 Compared with other imaging modalities such as computed tomography, EUS is superior in staging of esophageal tumors because of its higher spatial resolution, which allows to differentiate the esophageal wall layers. 16,17 Using EUS, the aim of this study was to investigate the more subtle changes of and injuries to the posterior wall of the left atrium, the periesophageal connective tissue, and the whole wall of the esophagus including mucosal alterations.…”
Section: Clinical Perspective On P 159mentioning
confidence: 99%
“…The proportion of tumors which are non-traversable varies from study to study, but may be up to 45 % [19,48,49]. Most non-traversable tumors are at least T3 tumors.…”
Section: Obstructing Tumors: What Are the Options For Eus Staging?mentioning
confidence: 99%
“…However, the miniprobes' high frequency may limit their ability to evaluate the full depth of tumor penetration and regional lymph node involvement. Nonetheless, at least one study has shown better T staging and comparable N staging with miniprobe EUS compared to conventional EUS in patients with both traversable and non-traversable tumors [48].…”
Section: Obstructing Tumors: What Are the Options For Eus Staging?mentioning
confidence: 99%